2018
DOI: 10.15252/msb.20188190
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput discovery of functional disordered regions: investigation of transactivation domains

Abstract: Over 40% of proteins in any eukaryotic genome encode intrinsically disordered regions (IDRs) that do not adopt defined tertiary structures. Certain IDRs perform critical functions, but discovering them is non‐trivial as the biological context determines their function. We present IDR‐Screen, a framework to discover functional IDRs in a high‐throughput manner by simultaneously assaying large numbers of DNA sequences that code for short disordered sequences. Functionality‐conferring patterns in their protein seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
155
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(182 citation statements)
references
References 60 publications
16
155
0
Order By: Relevance
“…For example, we found IDRs that show constraint on glycine and arginine content, but these may reflect the real constraint on planar-pi interactions and are not fully captured by either of these features. In the future, we could exhaustively search for protein sequence features that best explain the evolutionary patterns as was done for features of activation domains that explain reporter activity (Ravarani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found IDRs that show constraint on glycine and arginine content, but these may reflect the real constraint on planar-pi interactions and are not fully captured by either of these features. In the future, we could exhaustively search for protein sequence features that best explain the evolutionary patterns as was done for features of activation domains that explain reporter activity (Ravarani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, experimental developments in large‐scale mutagenesis (Staller et al , ), phage display (Davey et al , ; Sundell et al , ), ligand foot‐printing and mass spectrometry (preprint: Parker et al , ) are beginning to provide insights into functional elements within disordered regions. Alongside these experimental approaches, hybrid experimental–computational approaches such as IDR‐Screen that exploit machine learning (Ravarani et al , ) will allow for new ways of uncovering mechanistic interpretation of mutations. Lastly, a more principled construction of multiple sequence alignments from which conservation is inferred can also improve predictions.…”
Section: Mutfunc Allows Mechanistic Predictions Of Variant Effect Formentioning
confidence: 99%
“…For example, while AD sequences can be moderately conserved in closely related orthologs , no common sequence motif has been found when comparing ADs from different transcription factors. In addition, small-scale screens for ADs using random sequences of varying length fused to a DNA binding domain found that ~1% of these sequences encoded AD function (Abedi et al, 2001;Erkine et al, 2002;Ma and Ptashne, 1987a;Ravarani et al, 2018;Ruden et al, 1991). Finally, prior work analyzing natural and synthetic ADs have found several sequence features that correlate with AD function including intrinsic disorder, the presence of acidic, hydrophobic, and aromatic residues, low sequence complexity, net negative charge (or lack of positive charge) and, in some cases, alpha helix propensity (Brzovic et al, 2011;Dyson and Wright, 2016;Erkina et al, 2016;Ma and Ptashne, 1987a;Ravarani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%